Why knowing what to do is not enough : a realistic perspective on self-reliance (2019)
This book is a translation and adaption of the Dutch report ‘Weten is nog geen doen’, published by the Netherlands Scientific Council for Government Policy (WRR) in 2017. The report was presented to the State Secretary of Security and Justice, Klaas Dijkhof, on 24 April 2017. In it, the WRR recommends the Dutch government to take a realistic approach on people’s mental capacities when designing rules and institutions. On 22 January 2018, the government gave its formal response in a Memorandum to Parliament, in which it embraced a more realistic approach and announced that new policies will be subjected to a ‘capacity to act test’. More information is available on the WRR website: https://english.wrr. nl/topics/self-reliance. This publication was written by Anne-Greet Keizer, Will Tiemeijer and Mark Bovens. Together they formed a project group, chaired by member of the Council Mark Bovens and coordinated by Anne-Greet Keizer. The group was assisted by interns Gijs Custers, Rodinde Pauw, Rosalie Joosten, Vivian van Wingerden, Emma Hartholt and Maxime Hensels. The original Dutch publication has been adapted for an international audience, but not updated. This book is the product of an extensive process of consultation and analysis. In addition to studying the academic literature, we conducted more than 90 interviews with experts, policymakers and stakeholders. We are very grateful for their time and effort. Their names are listed at the end of the book. Special thanks go the experts who were prepared to read and comment at length on an earlier version of this book. The theoretical chapters were reviewed by Prof. Dr. Denise de Ridder and Prof. Dr. Jaap Denissen. In the final phase, part of the publications was discussed with Prof. Dr. Kees van den Bos, Prof. Dr. Wilco van Dijk, Prof. Dr. Michiel Scheltema and Mr. Reinier van Zutphen.